Life cycle assessment and economic analysis of carbon sequestration through pyrolysis of invasive alien plants - Van Schoor, Annalie Ula-Caye (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.